Placenta accreta in the first trimester of pregnancy - Sagástegui Ponsignon, Carmen (2015)
Tthe case of a woman with abdominal total hysterectomy for post abortion persistent vaginal bleeding is presented. Pathology revealed placent accreta. She presented urological vesical and ureteral complications related to the surgical procedure. We review the risk factors and complications associated to placenta accreta.